Experimental Practices. Humanities and Arts in the Process of Constructing Knowledge for the Data-based Society - Krawczak, Michał; Jelewska, Agnieszka (My University, 2018)
Accelerating progress in the development of technological tools, the achievements of the sciences, and above all the ways of collecting and modelling data, are significantly changing the mechanisms of knowledge construction. The humanities, together with related artistic-research practices, are becoming a crucial part of the process of analyzing and interpreting such data, with a focus on their social and cultural impact. Thus, the humanities have been entering into synergic relations with science and technology.
Keywords: transdisciplinary research; art&science; art as research; data-driven society; data-based society; interactive art